Biodegradation of Carbendazim using Four bacterial Strains. - Sara Nadum Hameed / Alaa Hassan Al-Farttoosy ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The soil microorganisms were enriched with MBC by using different concentrations 250 ppm for 40 days. Four bacterial strains were isolated based on morphological, and molecular identification. The Polymer chain reaction technique (PCR) proved that the isolated bacteria are: Pseudomonas putida, Pseudomonas aeruginosa, Klebsiella pneumonia, and Enterobacter cloacae. MBC-degradation strains were studied using 1000 ppm MBC in mineral salt media. The highest growth rate was recorded by K. pneumonia strain, reaching 2.257/day, followed by P. aeruginosa 2.25/day, then P. putida 2.1/day, and the lowest growth rate was for E. cloacae 83.0/day.